KAPASSARINHO (DATURA STRAMONIUM) EFEITO E REAÇÕES CONTRAVERSAS - Kinhama, Victorino Correia; Chimuco, Marinela Sepalanga Vasco; Kapele, Madalena Bumba Correia Kinhama (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
Articles The work was aimed at the bibliographical description of the Kapassarinho plant (Datura Stramonium), to understand its countervailing effects since there are few studies mentioned, its extracts are complex mixtures consisting of several chemical classes of natural products. Kapassarinho is a common name in Angola and is found in the interior of the country classified as a weed. To carry out this work we used the methodology of document review based on the review of books, scientific articles, magazines and other existing materials that addressed content of great contribution to this theme. There is no clarity about the origin of this plant, but if Africa is the cradle of humanity is where it originated and spread throughout the world, in Angola besides the medicinal aspects, young people use this plant as a drug. The seed of this species is highly effective against Colletotrichum gloeosporioides, although it is a host plant for many diseases and pests affecting crops of the Solanácea Family.